Gerakan Politik Lokal Waria dalam Perjuangan Hak Bekerja - Ricky Santoso Muharam; Ari Pradhanawati; Fitriyah Fitriyah; Supratiwi Supratiwi (Badan Strategi Kebijakan Hukum, 2023)
The enactment of Regional Regulation No. 1 of 2014 concerning the Handling of Vagrants and Beggars, which has an impact on the waria (transgender) community of Yogyakarta. Most work as buskers and (art workers) reject the existence of Gepeng Regional Regulation. This rejection was based on the fact that the waria community refused to be categorized as vagrants and beggars. Research using qualitative with case studies. This research focuses on the strategy of the Yogyakarta transgender political movement by forming an advocacy coalition in response to the implementation of the Gepeng Regional Regulation which is considered to have an impact on the waria community working on the streets. The results of this study found that carrying out resistance or rejection actions was carried out in two ways. First, build a network of advocacy coalitions between communities. Second, Strategy through the media. The enactment of Perda Gepeng gave rise to two advocacy coalitions, namely the IWAYO, advocacy coalition which was formed as a result of the consolidation of several waria communities in Yogyakarta and the Gepeng Regional Caucus Coalition consisting of various organizations, NGOs and various communities that support the struggle in rejecting the Gepeng Regional Regulation by trying to influence government decisions that are considered damaging democratic values and harming the poor.